SOSIALISASI PEMILIH PEMILU DI SEKOLAH MENENGAH KEJURUAAN MELALUI PENGGUNAAN ADOBE FLASH - Hazizah, Hazizah; Fadilah, Fadilah; Mering, Aloysius (Universitas Tanjungpura, 2022)
AbstractThe aims of this research were to determine: (1) the message design that would be used inthe development of adobe flash for the socialization of vocational students in Sintang, (2)the implementation of the message design that would be used in the development of adobeflash for the socialization of vocational students in Sintang, (3) Interest in participating inthe general election of SMK students in Sintang, (4) Awareness and positive attitude ofSMK students in Sintang towards the election after using Adobe Flash. This research is adevelopment research using the Borg Gall development procedure. Data obtained frominterviews, observations, questionnaires and documentation. The results showed that: (1)the design of adobe flash for the socialization of vocational students in Sintang was carriedout through the Borg and Gall stages, (2) the implementation of the socialization ofvocational students in Sintang using adobe flash was included in the very appropriatecategory, (3) the interest of vocational students in Sintang towards the election after usingadobe flash is in the good category, and (4) the critical attitude of vocational students inSintang has raised awareness and a positive attitude towards the election after using adobeflash is in the very good category. Therefore, it is hoped that the government will programsocialization media that can attract SMK students in Sintang to take part in the election.Keywords: Election Voter Socialization, Vocational Middle School, Using Adobe Flash